2014
DOI: 10.1902/cap.2013.130011
|View full text |Cite
|
Sign up to set email alerts
|

Use of Platelet‐Rich Fibrin Membrane as a Palatal Bandage

Abstract: Introduction: Free gingival grafting is one of the most common techniques used to increase the dimensions of keratinized tissue (KT). The palatal donor sites heal with secondary intention, require a longer time, and cause discomfort to patients. This case series describes the use of platelet‐rich fibrin (PRF) membrane as a palatal bandage to cover donor sites. To the best of the authors’ knowledge, this is the first report that describes the use of PRF membrane as a palatal bandage. Case Series: Five patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 12 publications
3
36
0
Order By: Relevance
“…These data agree with results from Aravindaksha et al, 19 who reported complete healing at week 3 in 100% of PRF‐treated patients.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These data agree with results from Aravindaksha et al, 19 who reported complete healing at week 3 in 100% of PRF‐treated patients.…”
Section: Discussionsupporting
confidence: 92%
“…Another interesting finding from the present study is the lower degree of D and the minor CFH observed in the test group. This observation cannot be compared with others in the literature because the only other study of PRF palatal bandages 19 did not evaluate the patients’ morbidity.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Earlier studies with PRF have demonstrated faster healing and bone fill when used in the treatment of cystic cavity,[20] sinus lift procedures,[24] socket preservation,[20] palatal bandage[25] and mandibular Grade II furcation defects. [26]…”
Section: Discussionmentioning
confidence: 99%